Sistem Pendukung Keputusan Penentuan Jurusan SMA Menggunakan Metode ELECTRE - Rusito Rusito; Hendri Surjani (STMIK Budi Darma, 2018)
Student majors in secondary schools are not only determined by academic ability but must also be supported by interest factors, since the characteristics of a science demand the same characteristics of those who study them. In accordance with the applicable curriculum throughout Indonesia, the majors available in SMA include Natural Sciences (IPA), Social Sciences (IPS), and Linguistics. The majors will be tailored to the student's interests and abilities. The criteria for determining this department are based on the value of academic achievement, competency test scores and specialization. The number of students and various matapelajaran also affect the speed in determining student majors. In terms of selection of majors needs to be done with a mathematical method in order to run quickly and fairly, for example with the method of ELECTRE. The ELECTRE (Elimination Et Choix Traduisant la realitE) method is one of the most effective methods for MADM with qualitative and quantitative features. Looking from the above case then the author tries to solve the problem of selection with the model of Multi Attribute Decision Making (MADM). This research will apply an Electre method to address the determination of the majors quickly. This research uses Borg & Gall's method of research and development (1987). The results of this study is the results of expert system validation shows the value of 2.8 is between 2.51-3.25 which belongs to the category Valid and validation of the user shows the value of 3.22 is between 2.51 - 3.25 which belong to the category Effective .